Dietary patterns and onset of obesity among medical students in Banja Luka - Suzana Savić; Gordana Tešanović; Larisa Gavran; Saša Stanivuković (Биомедицинска истраживања, 2020)
Introduction: The World Health Organization (WHO) revealed that in 2016 more than 1.9 billion adults, 18 years and older, were overweight. Over 650 million of them were obese. Diet quality in university students is determined by factors such as family, food availability and meals in student canteens. The purpose of this study was to investigate frequency of obesity and its relation to dietary habits, gender and age/year of study among medical students at the Faculty of Medicine of the University of Banja Luka. Methods: This is a prospective and descriptive study conducted among 1-6 year student population at the Faculty of Medicine of the University of Banja Luka. The study includes a validated survey instrument Youth Risk Behavior Survey Questionnaires. The study was approved by the Ethics Committee of the Faculty of Medicine and carried out as an anonymous survey during the winter term of the academic year 2017/2018. Results: Out of the total 601 students, the research sample included 543 students: 327 female (60.2%) and 216 (39.8%) male students. The majority of them (62.1%) fell within healthy weight range, and 2.4% were class 1 obesity. Most of female students (75.7%) had healthy weight while their male counterparts (73.2%) were overweight. To sum up, 57.5% of them consumed breakfast every day: female students significantly more (60.6%) than male students (51.9%). Third-year students (59.4%) had breakfast most frequently compared to the fifth-year students (55.0%) who ate it the least. Conclusion: The study found a high prevalence of overweight among male respondents compared to their female counterparts, who had predominantly healthy weight.
Keywords: medical student; nutritional status; dietary patterns